LISTENING AND SPEAKING SKILLS AS LEARNING AND TARGET NEEDS IN BUSINESS ENGLISH PROGRAM FOR TOUR GUIDE DIPLOMA STUDENTS IN KENYA. - Douglas Ondara Orang'i (Journal of Applied Linguistics and Literature, 2021)
Any ESP course design should be hinged on elaborate needs of learners so as to come up with a course that is inclusive. This can only be achieved after conducting a needs analysis that takes into consideration the views of all relevant stakeholders. Needs analysis is an important step in any syllabus design and particularly that which touches on ESP. That notwithstanding, ESP practitioners are ignoring this very paramount step when designing a course. Consequently, this paper looked at the target and language learning needs of tour guide learners pursuing an ESP course in Kenya from the students’ perspective, teachers’ perceptions and employers’ perceptions as far as the ESP course offered to learners is concerned. This paper focuses on listening and speaking skills. The paper based its theoretical framework on Munbian (1978) Approach and Learning Centered Approach by Hutchinson and Waters (1987). A descriptive research design is adopted in the study. The data analysed in this paper is got from Orang’i (2013). This paper is an attempt to show that learners can very ably articulate their needs and that teachers too can give their perceptions on learners’ needs thanks to their experience in the field. Equally, employers as has been seen in this paper also have a say on the ESP courses offered to learners. It is shown that needs analysis is an important stage in needs analysis that should not be overlooked and when it is conducted, it should involve all the stakeholders in order to come up with needs that are encompassing.